Cathodic Radical Cyclisation of Aryl Halides Using a Strongly‐Reducing Catalytic Mediator in Flow. Issue 35 (18th July 2022) - Folgueiras‐Amador, Ana A.; Teuten, Alexander E.; Salam‐Perez, Mateo; Pearce, James E.; Denuault, Guy; Pletcher, Derek; Parsons, Philip J.; Harrowven, David C.; Brown, Richard C. D.
Abstract: Electro‐reductive radical cyclisation of aryl halides affords the corresponding hetero‐ and carbo‐cycles in an undivided flow reactor equipped with steel and carbon electrodes using an organic mediator. A dissolving metal anode is not needed, and the mediator can be employed in a sub‐stoichiometric amount (0.05 equiv), increasing the practical utility of cathodic radical cyclisation. The methodology is applied to O‐, N‐, and C‐tethers, yielding tricyclic fused and spiro systems. In the absence of mediator, the major pathway is hydrogenolysis of the C−X bond, a 2 e − process occurring at the cathode. Predominance of the radical pathway in presence of a strongly reducing mediator (M ) is consistent with homogeneous electron‐transfer in a reaction layer detached from the cathode surface, where the flux of M .− leaving the electrode is such that little aryl halide reaches the cathode. Abstract : Cathodic radical cyclisations of aryl halides have been achieved in an undivided flow electrolysis cell, using phenanthrene as mediator in loadings down to 0.05 equiv, and without the requirement for a sacrificial anode. It is proposed that mediated homogeneous electron transfer proceeds in a reaction layer detached from the cathode, accounting for the observed selectivity.